2021
DOI: 10.5811/westjem.2021.3.49770
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender in Nurse-Resident Interactions: A Mixed-methods Study

Abstract: Introduction: The role of gender in interprofessional interactions is poorly understood. This mixed-methods study explored perceptions of gender bias in interactions between emergency medicine (EM) residents and nurses. Methods: We analyzed qualitative interviews and focus groups with residents and nurses from two hospitals for dominant themes. An electronic survey, developed through an inductive-deductive approach informed by qualitative data, was administered to EM residents and nurses. Quantitative analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…A recent mixed-methods study that utilized qualitative interview-based findings to build a quantitative survey of emergency room nurses and resident physicians found that gender had a significant impact on interprofessional interactions. 14 Although nurses expressed greater frustration with male residents, who they perceived to be more dismissive and less collaborative, female residents reported more frequent questioning of their clinical plans by nurses-especially by female nurses. While nurses may have perceived their interactions with female residents to reflect a greater collaborative ability, the female residents felt that such interactions reflected a decreased confidence in their abilities.…”
Section: The Surgeon-staff Relationshipmentioning
confidence: 99%
“…A recent mixed-methods study that utilized qualitative interview-based findings to build a quantitative survey of emergency room nurses and resident physicians found that gender had a significant impact on interprofessional interactions. 14 Although nurses expressed greater frustration with male residents, who they perceived to be more dismissive and less collaborative, female residents reported more frequent questioning of their clinical plans by nurses-especially by female nurses. While nurses may have perceived their interactions with female residents to reflect a greater collaborative ability, the female residents felt that such interactions reflected a decreased confidence in their abilities.…”
Section: The Surgeon-staff Relationshipmentioning
confidence: 99%
“…Title and abstract screening excluded 646 citations, resulting in 21 records eligible for full‐text screening. Five were excluded based on study objectives, 23–27 four for study design, 28–31 one because it was a duplicate, 32 and one for not including EM residents 33 . Ten records underwent data extraction 12,15,32,34–40 …”
Section: Resultsmentioning
confidence: 99%
“…Another common theme was the challenging of resident authority and competency by nursing staff. Previous studies explored the complex, gender‐based relations between EM residents and nurses, demonstrating that women residents perceived gender‐based discrimination perpetrated by nurses 12,26 . Women residents reported the need to provide an explanation when administering orders to ensure completion of said orders as well as general questioning of their abilities by nursing staff.…”
Section: Discussionmentioning
confidence: 99%